Generation control circuit for photovoltaic modules. - Shimizu, T. (IEEE Transactions on power electronics)
Photovoltaic modules must generally be connected in series in order to produce the voltage required to efficiently drive an inverter. However, if even a very small part of photovoltaic module (PV module) is prevented from receiving light, the generation power of the PV module is decreased disproportionately. This greater than expected decrease occurs because PV modules which do not receive adequate light cannot operate on the normal operating point, but rather operate as loads. As a result, the total power from the PV modules is decreased if even only a small part of the PV modules are shaded. In the present paper, a novel circuit, referred to as the generation control circuit (GCC), which enables maximum power to be obtained from all of the PV modules even if some of the modules are prevented from receiving light. The proposed circuit enables the individual PV modules to operate effectively at the maximum power point tracking, irrespective of the series connected PV module system. In addition, the total generated power is shown experimentally to increase for the experimental set-up used in the present study